The Psychology of Ants in the Work of Ramón y Cajal - Ibarz-Serrat, Virgili (2017)
Santiago Ramón y Cajal explains that in order to investigate the psychology of ants, we must consider the data related to tropisms, perceptions, associative memory, reflex acts, superior instincts, etc. He divides the ants into two large groups: poliopsic ants, whose eyes have eight hundred or more corneal facets, which see well o regularly, and oligopsic ants that look very little and whose corneal facets range from seventy to five hundred. Cajal concludes that oligopsic ants have a great sensorial poverty. Except tact and smell, which are very developed, the remaining senses render confused and fragmented observations of the outside world. Poliopsic ants, on the other hand, are sensitive to colors and particularly impressed with black.